Pau-branco (Cordia oncocalyx Allemão): etnobotânica, usos e conservação - Girão, Enio Giuliano (2022)
We live in a world of decreasing ecological diversity. We extract energy, materials, and organisms from nature and modify landscapes at unsustainable rates. These activities have resulted in increasing rates of degradation and loss of the natural systems in which our species are embedded. A solution that minimizes species extinction while being far-reaching and economically viable seeks an alternative in the concept of flagship species. By raising the profile of a particular species, more support can be raised for biodiversity conservation. By drawing public attention to the endangered status of a certain, more attractive species, the entire ecosystem around it has a better chance of being conserved. We chose the "pau-branco" (Cordia oncocalyx Allemão) as the key species because of its attractiveness (floral architecture) and ornamental potential with the public (leafy tree with heart-shaped fruits and flowers), the population's knowledge about the species and its vulnerability or ecological value. The investigation of the theme leads to research objectives in areas whose understanding requires interdisciplinarity. The proposal aims to systematize elements of botanical history, uses, practices, and other knowledge about the pau-branco, including contributions from the scientific and popular (empirical knowledge) communities, technicians, furniture makers, and farmers. Therefore, we divided the work into 4 (four) chapters: 1. Scientific expeditions through Ceará and their reports on the Pau-branco (Cordia oncocalyx Allemão); 2. Pau-branco (Cordia oncocalyx Allemão): ethnobotany and strategies for conservation; 3. Occurrence of pau-branco (Cordia oncocalyx Allemão) in the Caatinga biome, with emphasis on rural settlements in the State of Ceará; 4. Evaluation of the quality aspects of pau-branco (Cordia oncocalyx Allemão) and other woods from the Caatinga. Different methodologies are adopted in each chapter, such as the Humboldtian method; botanical report by literature review and systematization; multivariate statistics and Check-all-that-Apply (CATA). At the end of the study, we hope that the research can contribute to stimulate academic interest in the species and its multiplication in the context of Caatinga, placing it in a range of rational uses (conservation), valuation by the scientific community and society, stimulating studies on pau-branco and other species in partnership with universities and research institutes.